If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+4-8r=-3r-18-2
We simplify the equation to the form, which is simple to understand
1+4-8r=-3r-18-2
We move all terms containing r to the left and all other terms to the right.
-8r+3r=-18-2-1-4
We simplify left and right side of the equation.
-5r=-25
We divide both sides of the equation by -5 to get r.
r=5
| x+4*3+2=12 | | -2(4s-3)-6=-3(4s+4)-4 | | 36+3n=-3(4-3n) | | x+2*6=42 | | 8/1/2= | | 7x+6-9(x+1)=5x+3 | | 7(x-7)=-25-5x | | -8(8k+2)=-4k-16 | | 16x^2-72x-49=0 | | -5(-4+2v)=-50 | | 6(5x-2)-3(3x-16)=5(4x+3)-7 | | -6(3p-6)=-34-8p | | (g)(g)+6g=27 | | 10x+240=60x | | -5(x-2)=16-8x | | 5.07-3.21(2x-1)=7-2.37x | | 2(1+4k)+2k=9(4+3k) | | 0.10x+240=60x | | 0.27(6)+0.03x=0.09(18+x) | | (X)(x)+16x+28=0 | | (-8a)(3b^3)(5a^2b)=0 | | 2(x-7)=3x-9 | | (-ba)(3b^3)(5a^2b)=0 | | 2(x-7)=3-9 | | -2=4+2x+4x | | v^2-v=21+3v | | 6X-(5X+4)=2X-28 | | 29+4x=4(7+7x)+1 | | (X)(x)+16x=-28 | | 8w^4*-w^7= | | 3x^2-28x=55 | | -p*-9p^2= |